PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL DISCOVERY LEARNING LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI SISTEM KOORDINASI KELAS XI SMA - Welly Juli Ariesta; Wan Syafi’i; Arnentis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to Produce Student Learning Sheet (LKPD) Based Discovery Learning Learning Model to Increase Critical Thinking Ability in Material of Class XI Coordination System of SMA. This research is conducted in Biology Education Laboratory of PMIPA Faculty of Teacher Training and Education Universitas Riau and SMAN Plus Riau Province. This research was conducted from March to June 2017. The research type used in this research is referring to Reseach and Development (R & D) approach using ADDIE model consist of five stages: analyze, design, development, implementation and evaluate. This research is only done until development stage. The instrument used is validation sheet and questionnaire of respondent. Further trial is limited to 12 students of Biology education and 24 students of class XI SMAN Plus Riau Province. Research data were analyzed using descriptive analysis. LKPD validation result based on Discovery Learning Learning model for coordination system material seen from 3 aspect that is content feasibility aspect, design aspect, and pedagogic aspect. The validity value of LKPD based on Discovery Learning Learning model on the design aspect that is with the score of 3.31 category is very valid, the pedagogic aspect validity value is 3.38 category is very valid, while the validity value on feasibility aspect of content with score of 3.25 category valid. Student responses on all aspects are categorized very well with a score of 3.58 and the response of learners on all aspects is categorized very well with a score of 3.38Keyword: Learner Worksheets, a model of Discovery Learning learning and critical thinking